Composition and Properties of Drilling and Completion Fluids. - Caenn, Ryen (Elsevier Science, 2011)
The petroleum industry in general has been dominated by engineers and production specialists. The upstream segment of the industry is dominated byÈdrilling/completion engineers. Usually, neither of those disciplines have a great deal of trainingïn the chemistry aspects of drilling and completing a well prior to its going on production.ÈThe chemistry of drilling fluids and completion fluids have a profound effect on the success of a well. For example, historically the drilling fluid costs to drill a well have averaged around 7% of the overall cost of the well, before completion.